Effect of polymers on in-vitro performance of eplerenone sustained release matrix tablets - Sunil Reddy; Vinay Katakam; Jagan Mohan Somagoni; Pavan Panakanti; Sathish Dharani; Madhusudan Rao Yamsani (Archives of Global Professionals, 2012)
Objectives: The intention of the present study was to design and assess oral sustained drug delivery systems for Eplerenone, using Cellulose and natural polymers as release modifiers in the form of matrix tablets. Material and methods: Matrix tablets containing cellulose polymers like HPMC K4M, HPMC K15M, NaCMC and natural polymers like Guar Gum, Xanthan Gum, and Karaya Gum were prepared by wet granulation technique using PVP K60 as a tablet binder. Results: The optimized formulation (F1) contains 1: 0.70 ratio (D: HPMC K4M) and (F4) contains 1:1 ratio (D: Guar gum) respectively. The in-vitro release kinetic studies of prepared matrix tablets with both the polymers were studied. The kinetic treatment illustrate that the optimized formulation (F1 and F4) followed zero order kinetics with release exponent (n) 0.87. Drug content in the tablets and amount of drug released were estimated by reported HPLC method. The FT-IR and DSC studies did not show any interaction of drug with the excipients used in the formulation. Conclusion: The results clearly indicated that Eplerenone could be successfully prepared using an appropriate ratio of cellulose polymers like HPMC K4M, and natural gums like Guar gum in the form of matrix tablets